EMPLOYEE PERFORMANCE REVIEW OF COMPETENCE, MOTIVATION, AND WORK DISCIPLINE AT PT INDAH LOGISTIC SOLO BRANCH - Joko Purwanto; Sri Hartono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Developments in the fast-paced economy and superior human resources are a separate value for a company. Companies must be able to improve and make plans and evaluate each other's performance so that the company develops and has the value of public trust through its resources. This study aims to determine the effect of competence, motivation, and work discipline on employee performance at PT. Indah Logistics Solo Branch. The research approach used is descriptive quantitative. Non-probability sampling was used in this study with a saturated sample method of 58 irespondents. iThe ianalysis iis imultiple linear regression. The iresult is that competence has a positive and significant effect on employee iperformance iwith ia it-value = 1.676 > it-table value = 1.674. Motivation has a ipositive iand isignificant ieffect ion iemployee performance with ia value of t icount = 1.789 > it itable = 1.674 iand discipline has ia positive and significant effect on employee performance with a value of t count = 4.455 > it itable = 1.674. . Keywords: Employee performance, competence, motivation, work discipline